Personality Traits Differentiate Subgroups of Criminal Offenders With Distinct Cognitive, Affective, and Behavioral Profiles - Dargis, Monika (Criminal justice and behavior, 2018)
Mental illness and substance use disorder are prominent among jail and prison inmates. Developing more effective mental and behavioral health treatment approaches for incarcerated criminal offenders is a critical step toward reducing rates of recidivism and relapse following release. Specifying subgroups of offenders who differ in cognitive, affective, behavioral, and demographic characteristics could facilitate more targeted and effective treatment approaches. Accordingly, this study utilized model-based cluster analysis to identify subgroups of offenders in a large sample of incarcerated male offenders (n = 2,388) using broad personality traits. Six subgroups of offenders emerged based on personality scales related to positive affect, negative affect, and behavioral control. Subsequent analyses revealed significant differences between groups on measures of cognitive ability, affect dysregulation, antisociality, substance use, and impulsivity. These findings provide insight into potential treatment and intervention strategies to target the specific needs of distinct subgroups of incarcerated offenders.